PERAN BAITUL MAAL WAT TAMWIL UGT SIDOGIRI SURABAYA DALAM MENGATASI DAMPAK NEGATIF PRAKTIK RENTENIR - Amaliana Afidah; Karjadi Mintaroem (Universitas Airlangga, 2019)
This research aims to know the role of BMT UGT Sidogiri been fullest or not in overcoming the negative impact of loan sharks in the region of Demak prakti East. The approach used was qualitative descriptive type approach strategy case studies. This strategy was chosen because there are things that would like to be known by researchers associated with the formulation of the problem. The required data in the research is primary data and secondary data. Technical data collection performed while field research in BMT UGT Sidogiri and around the region of Demak. Data collection is done with the interview and documentation. Supporting data come from studies and journal literature through internet searches. Data analysis technique used is the reduction of data to get a conclusion. The results obtained by researchers based on interviews that BMT has not been significantly instrumental in freeing people from the bondage of moneylenders. Inadequate efforts made BMT in freeing society from moneylenders who practices tend to be more proactive in offering their services to merchants is evidenced by the large number of traders who prefer to connect with the moneylenders.Keywords: BMT Sidogiri UGT, The Role Of BMT, The Impact Of Loan Sharks, Practices Of MoneylendersREFERENCESAnselm Strauss dan Juliet Corbin. 1997. Dasar-Dasar Penelitian Kualitatif Prosedur, Tekhnik, dan Teori. Surabaya: Bina Ilmu Ofset.Al-Baraq, A. (2010). Bukan Dosa Ternyata Dosa. Jakarta: Pustaka Grahatama.Afandi, Muhammad Yazid, Fiqh Muamalah dan Implementasinya Dalam Lembaga Keuangan Syariah. Yogyakarta: Logung Pustaka, 2009Aisyiyah. Majelis Ekonomi dan Ketenagakerjaan. Diperoleh 21 Maret 2016 darihttp://www.aisyiyah.or.id/page/majelis-ekonomi-dan-ketenagakerjaan.htmlAl-Afriqi, Ibn Mansur. Lisan al – A’rab. Jilid VIII. Beirut: Dar al-SadrAl-Fasy Allal. 1993. Maqashid asy-Syariah al-Islamiyah wa Makarimuha, KSA: Darul Garb Al-IslamyAntonio, M. S. (2001), ). Bank Syariah dari Teori ke Praktik. Jakarta: Gema Insani.Arikunto, S. (1998). Prosedur Penelitian : Suatu Pendekatan Praktek. . Jakarta: Rineka Cipta.Ali Moch.Aziz. 2009. Ilmu Dakwah Edisi Revisi. Jakarta: Kencana Al-QuranAmalia, Euis, Sejarah Pemikiran Ekonomi Islam, Jakarta: Pustaka Asatruss, 2005, H.16Aziz Amin, Muhammad, Penanggulangan Kemiskinan Melalui BMT, Pinbuk Press, 2004, H.142Andri, Soemitra, Bank & Lembaga Keuangan Syariah, Kencana, Jakarta, 2014Antonio, Muhammad Syafi’I, Bank Syariah: dari teori ke praktik. Jakarta: Gema Insani, 2001Aries, Mufti. Peranan MES dalam mengembangkan Lembaga Keuangan Syariah di Indonesia,2002, Ed, 111, Vol.111, H.14Basrowi dan Suwandi. 2008. Memahami Penelitian Kualitaif. Jakarta, Rineka Cipta.Basyir, Ahmad Azhar, Asas-asas hukum Muamalah, Yogyakarta: Fakultas HukumUII, 1983Djazuli, A, & Janwari, Y. (2002). Lembaga-Lembaga Perekonomian Umat: SebuahPengenalan.. Jakarta: Raja Grafindo PersadaDjuwaini, D, & Qudsy, S.Z. (2008). Pengantar Fiqh Muamalah. Jakarta: Pustaka PelajarGhafur, Muhammad W, Memahami Bunga dan Riba Ala Muslim Indonesia. Sleman: Biruni Press, 2009Ginting, J. (2014). Hukum Perbankan dan Tindak Pidana Pencucian Uang. repository.ut.ac.id.Hertanto, dkk, Panduan Praktis Operasional Baitul Maal Wattamwil. Bandung: Wiroso. 2005Hadi, Sutrisno, Mettodologi Research. Yogyakarta: Fakultas Psikologi UGM, 1983Hertanto, dkk, Panduan Praktis Operasional Baitul Maal Wattamwil. Bandung: Wiroso. 2005Hisyam, M.Said Hisyam. 2014. LKM Panduan LKM BMT. CV Alba Multi SIdrus, Muhammad. (2007). Metode Penelitian Ilmu-Ilmu Sosial (Pendekatan Kualitatif dan Kuantitatif). Yogyakarta: UII Press Yogyakarta.Imaniyati, N. S. (2010). Aspek-Aspek Hukum BMT (Baitul Maal wat Tamwil). Jakarta: Citra Aditya Bakti.Joelarso, BMT Summit 2014, Yogyakarta, Universitas Gajah Mada, 7 NovemberMuslic, Ahmad Azhar, Asas-Asas Hukum Muaamalah. Jakarta, 2013Moleong, Lexy, J. 1989. Metodologi Penelitian Kualitatiif. Bandung: PT. Remaja Rosdakarya.Nafik H.R, Muhammad, Benarkah Bunga Haram?, Surabaya, Amanah Pustaka 2009Nakubo, Cholid Nakubo dan Abu Ahmad, Metode Penelitian. Jakarta: Bumi Aksara, 2005Nugroho, M. (2009). Usaha Mikro, Kecil dan Menengah. Jakarta: Trisakti Press.Perhimpunan BMT Indonesia.(2011). Haluan BMT 2020Prastowo, Andi, Metode Peneliian Kualitatif dalam Perspektif Rancangan Penelitian, Yogyakarta: Arruz Media, 2011Sabwari, Sejarah Pemikiran Ekonomi Islam. Yogyakarta: PT. Dhani Bakti Wakaf, 1995Sholihin, A. I. (2013). Buku Pintar Ekonomi Syariah. Jakarta: Gramedia Pustaka Utama.Siahaan, M. (2015). Rentenir Penolong Pedagang Kecil? Jakarta: Elex Media Computindo.Subagyo,(2015), Bank dan Lembaga Keuangan Lainnya, Jakarta, Salemba Empat.Sugiyono, 2011. Metode Penelitian Kuantitatif Kualitatif dan R&. Bandung: Alfabeta.Sibarani, B. (2002). Rentenir. Jurnal Hukum & Pembangunan (http://jhp.ui.ac.id/index.php/home/article/view/1353), Vol 32, No 4.Siboro, I. K. (2015). Rentenir (Analisis Terhadap Fungsi Pinjaman Berbunga Dalam Masyarakat Rokan Hilir Kecamatan Bagan Sinembah Desa Bagan Batu) . Jom Fisip Vol. 2 No. Oktober.